2013
DOI: 10.3892/ijo.2013.2094
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific methylome screen identifies that NEFL is downregulated by promoter hypermethylation in breast cancer

Abstract: Aberrant hypermethylation of promoter regions in specific genes is a key event in the formation and progression of breast cancers, and an increasing number of marker genes have been identified. However, few genes which show methylation change in accordance with the progression of breast cancer have been identified. To identify genes which consistently undergo promoter methylation alterations as the tumor develops from a benign to a malignant form, genome-wide methylation databases of breast cancer cell lines f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
(31 reference statements)
0
11
1
Order By: Relevance
“…Sebastien Jauliac found that NFAT5 were expressed in invasive human ductal breast carcinomas and participate in promoting carcinoma invasion using cell lines derived from human breast and colon carcinomas [31]. NEFL has been shown to act as a tumor suppressor in the carcinogenesis of breast [32], [33]. However, we found significant association between these three SNPs and breast cancer risk only in stage I.…”
Section: Discussioncontrasting
confidence: 49%
“…Sebastien Jauliac found that NFAT5 were expressed in invasive human ductal breast carcinomas and participate in promoting carcinoma invasion using cell lines derived from human breast and colon carcinomas [31]. NEFL has been shown to act as a tumor suppressor in the carcinogenesis of breast [32], [33]. However, we found significant association between these three SNPs and breast cancer risk only in stage I.…”
Section: Discussioncontrasting
confidence: 49%
“…32 Also, abnormal genespecific promoter hypermethylation is closely associated with the occurrence and development of breast cancer. 33 The absence of Cosmc contributes to the expression of the Tn antigen through the regulation of T-synthase, which is related to the development and progression of various human diseases, including cancer. 34,35 For instance, a recent study has found that Cosmc deficient pancreatic cancer cell line Tn STn Promote breast cancer progression Figure 5 The molecular mechanism involving the regulatory roles of Cosmc/Tn/STn in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…siR-NEFL group. *p \ 0.05, **p \ 0.01, ***p \ 0.001, #p \ 0.05, ##p \ 0.01, ###p \ 0.001 heterozygous and homozygous deletions in a variety of common human cancers, including prostate cancer [30], breast cancer [31,32], and head and neck cancer (HNC) [27,33]. NEFL, a potential tumor suppresser [30,31,33], is associated with resistance to chemosensitivity.…”
Section: Discussionmentioning
confidence: 99%